2015
DOI: 10.15386/cjmed-455
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal hypertension in the ICU – a prospective epidemiological study

Abstract: The aim of this prospective study is to examine the frequency and the severity of intra-abdominal hypertension in a mixed ICU of the University hospital.MethodsA closed system for intravesical intermittent measurement of IAP was constructed.ResultsThe frequency and the severity of IAH were examined in the period from June 2009 to December 2012 in 240 ICU patients divided into 3 groups (patients submitted to elective surgery, emergency surgery, and medical patients) in the University Hospital. In the elective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the elective surgery group, there was 12.5% IAH, while in the emergency group, IAH was 43.75%, and in the medical patients, it was 42.5%. [10]…”
Section: Discussionmentioning
confidence: 99%
“…In the elective surgery group, there was 12.5% IAH, while in the emergency group, IAH was 43.75%, and in the medical patients, it was 42.5%. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Simonson et al (8) reported that higher survival rates may be possible with early interventions via education of health professionals in related departments about measuring and evaluation of IAP. Arabadzhiev et al (9) reported in their study with ICU patients that early decompression decreases mortality rates. Therefore, routine IAP evaluation in ICU population can reduce both mortality rates and length of hospital stay.…”
Section: Resultsmentioning
confidence: 98%
“…Dalfino et al [28] studied 123 patients with ICU hospitalization longer than 24 hours and observed that IAH was associated with age, accumulated fluid balance, shock, sepsis, and abdominal surgery, but only the first three were found to be independent risk factors. Another multicenter study, which analyzed 358 patients from 39 ICUs who included patients requiring mechanical ventilation for more than 6 hours, showed that 22% of patients without additional risk factors had IAH [39].…”
Section: Discussionmentioning
confidence: 99%